Sistem PID untuk Pengaturan Aliran Air pada Dua Tangki Penampungan - Kartika; Naqi, M. Fatan; Jannah, Misbahul; Misriana (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2025)
The stable and efficient management of water distribution remains a critical challenge in water storage systems, especially in applications requiring precise flow control. This study aims to design and implement a water flow control system based on the Proportional-Integral-Derivative (PID) algorithm to maintain stable flow rates and water levels in a storage tank. The system employs an HC-SRF04 ultrasonic sensor to monitor water level with an accuracy of 99.77%, and a YF-S201 flow sensor to measure water flow rate with an exceptional accuracy of 99.997%. All components are integrated and controlled by an Arduino Uno microcontroller, the system’s core processing unit. Flow rate regulation is achieved using Pulse Width Modulation (PWM) to control the water pump, driven by the PID algorithm with a target flow rate (setpoint) of 4 liters per minute (LPM). The optimal PID parameters are obtained using the Ziegler-Nichols tuning method, yielding the constants ????ₚ = 12.96, ????ᵢ = 1.102 seconds, and ???????? = 0.2755 seconds. Experimental results show that the system achieves a rise time of 0.296 seconds, an initial overshoot of 2.5%, and a settling time of 10 seconds. This system demonstrates strong potential to support water management efficiency and automation across industrial, agricultural, and household applications, offering fast and stable control responses to maintain flow rate setpoints under dynamic conditions.